2010
DOI: 10.1002/nbm.1614
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetisation transfer imaging in glioma: preliminary results

Abstract: Quantitative magnetisation transfer imaging (qMTI) is an extension of conventional MT techniques and allows the measurement of parameters that reflect tissue ultrastructure through the properties of macromolecule-bound protons; these include the bound proton fraction and the relaxation times of free and bound proton pools. It has been used in multiple sclerosis and Alzheimer's disease, and has shown changes in some of the parameters, particularly the bound proton fraction. The purpose of this pilot study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…ADC was higher in the tumor region, suggesting a lower cellularity compared with normal tissues. PSR was significantly lower in the tumor, which is consistent with a few previously reported observations that used different qMT acquisition methods . The k mf and k fm maps show clear contrast between GM and WM and higher values within the tumor, but the overall signal‐to‐noise ratios are much lower.…”
Section: Resultssupporting
confidence: 90%
“…ADC was higher in the tumor region, suggesting a lower cellularity compared with normal tissues. PSR was significantly lower in the tumor, which is consistent with a few previously reported observations that used different qMT acquisition methods . The k mf and k fm maps show clear contrast between GM and WM and higher values within the tumor, but the overall signal‐to‐noise ratios are much lower.…”
Section: Resultssupporting
confidence: 90%
“…wileyonlinelibrary.com/journal/nbm relaxation, consistent with extensive earlier literature and conventional explanations of lower relaxation rates in malignant and other rapidly growing tissues (19). The MT exchange rate k mf is significantly higher in tumors, consistent with previous reports (16)(17)(18). There is also a small increase in ADC, suggesting a lower cellularity in tumors.…”
Section: Resultssupporting
confidence: 90%
“…Tozer et al (40) reported reduced macromolecular pool fraction in human gliomas compared with normal-appearing white matter. Thus, given these previously published reports and the data presented here, future qMT-MRI studies designed to study the effects of various biophysical processes in breast cancer on PSR measurements are warranted.…”
Section: Discussionmentioning
confidence: 99%